2018
DOI: 10.1002/jsfa.8777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of farming system on donkey milk composition

Abstract: Extensive farming of dairy donkeys increased the fat content and fat-soluble vitamin concentration of milk and also altered the FA composition to a more favorable profile for human nutrition. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…This increase in the protein amount of the milk may be depending on the stage of the donkeys' lactation period and the effects of the farming system on the produced milk. It is known that in the early stages of lactation, protein level and fat level can be higher [31].…”
Section: Physicochemical Analysesmentioning
confidence: 99%
“…This increase in the protein amount of the milk may be depending on the stage of the donkeys' lactation period and the effects of the farming system on the produced milk. It is known that in the early stages of lactation, protein level and fat level can be higher [31].…”
Section: Physicochemical Analysesmentioning
confidence: 99%
“…It may also be important to ensure sufficient levels of vitamin supplementation, especially, for those animals that are primarily fed on dried forages [22]. Pastures may be helpful since, according to Valle et al [9], green forages can increase the vitamin liposoluble content of milk.…”
Section: Nutritional Requirementsmentioning
confidence: 99%
“…The third reason is related to the fact that a forage-based diet has an effect on milk quality. Few studies are available on this topic, but Valle et al [9] reported that pasture feeding increased the fat content and fat-soluble vitamin concentration of milk. Chiofalo et al [35] described how fresh meadow herbage vs. meadow hay feeding resulted in a higher polyunsaturated fatty acid concentration in the milk.…”
Section: Farm Management Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, vitamin E synthesis in plants broadly varies, according to plant species and season (higher during spring-summer than during fall-winter) ( Sattler et al, 2003 ). As for the donkey, only a few contributions report detailed effects of the dietary regime on comparative biochemical profile and health conditions, with emphasis on specific nutrient deficiencies ( Chiofalo et al, 2005 ; Cappai, Picciau & Pinna, 2013 ; Cappai et al, 2017 ; Girardi et al, 2013 ; Valle et al, 2017 , 2018 ). In fact, very little is known about reference intervals of circulating parameters for this species ( Zinkl et al, 1990 ; French & Patrick, 1995 ; Folch, Jordana & Cuenca, 1997 ; Mori et al, 2003 ; Caldin et al, 2005 ; Bana et al, 2011 ; Girardi et al, 2013 ; Laus et al, 2015 ; Burden et al, 2016 ; Da Silva et al, 2018 ; Santos et al, 2018 ; De Palo et al, 2018 ; Gloria et al, 2018 ; Barrio, Rickards & Thiemann, 2019 ).…”
Section: Introductionmentioning
confidence: 99%